“We are going to turn this place into a place!” Affective politics and everyday life in a pavement occupation in Cape Town - Jackson, Jinty (Department of Environmental and Geographical Science, 2023)
This empirically- based research contributes to a vibrant debate on the role of occupations in city-making in the Global South. Much scholarly debate, however, fails to engage with the embodied nature of resistance to power, nor how cities are transformed through affective encounters of the everyday in what might look like contingent and precarious spaces. While most of the research on occupation in Cape Town have focused on land occupation in peripheral areas, a small, but growing area of research focuses on the occupation of existing buildings of the inner and central areas. However, scant attention has been given to the occupation of public space in the inner city to date. This case suggests some, emerging ways in which this Southern City is transforming through informal inhabitation of interstitial spaces. It does so at a time when the appearance of tents and makeshift shelters under bridges, along unfinished highways and pavements are initially associated, initially with the Covid-19 pandemic. Yet the case study from which thesis departs is an unusual one: It began as an occupation of an abandoned building, but became a long-term land occupation outside it, after the group's eviction. Furthermore, it pre-dated the pandemic by several months and was part of an organised social movement insisting on the right to live close to the economic heart of the city and the social privileges this implies. Based on qualitative research over a five-month period, (including in-depth interviews, nonparticipant observation, and photography) this case study shows how the occupiers maintained a space that held not only lives but heterogeneous imaginaries, experimental practices. The micro-politics emergent from this site, forged through resisting efforts to regulate and displace them, is characterised, (inter-alia) by the insistence of being hom(ed) and homemaking – as opposed to “home-less”. In suggesting that an attentiveness to the everyday, affective politics of occupations moves beyond conventional readings of the occupations as a contestation between citizens and state, it will interest those engaged in social movements, occupations, and critical urban scholarship in the Global South.